(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Water soluble polysaccharides were extracted from seeds of Cassia alata. The galactomannan extraction was based on mechanical separation of the endosperm, water dissolution, centrifugation and precipitation with acetone and pet ether. In the current investigation found that water-soluble galactomannan consisting of D-galactose and D-mannose in the molar ratio 13. Methylation and hydrolysis of the galactomannan produced 2,3-di-0-methyl-D-mannose (1 mole), 2,3,6-tri-0-methyl-D-mannose (4 moles), and 2,3,4,6-tetra-0-methyl-D-galactose (2 moles). Partial acid catalysed hydrolysis of the seed gum gave four oligosaccharides epimelibiose, mannobiose, galactosyl mannobiose, and mannotriose. The characterized polysaccharides from the gum has the basic structure of galactomannans with a main chain of (1→4)-linked β-D-mannopyranosyl units to which single α-(1→6)-D-linked galactopyranosyl units.